Factors Affecting Twinning and the Impacts of Twinning in Cattle - Lisa Praharani (WARTAZOA, Indonesian Bulletin of Animal and Veterinary Sciences, 2019)
Efforts to increase cattle production can be done through increasing the population and productivity of cattle, one of which is through the birth of two offsprings per parent (twin). The incidence of twinning in cattle ranged 1-10%, and influenced by genetic/breed, parity, management, season of breeding. This paper presented factors and technology that increase twinning rate and the impacts of twin births in cattle. There are genetic and non genetic factors affecting twinning rate. Increased twin births can be done through some technologies such as selection, reproduction and management. The problems in twinnings are the high incidence of abortion, early embryonic loss, distochia, retained placenta, metabolic disorders, and ketosis resulting in longer calving interval. Intensive management to dam bearing twins can reduce the problems. Economically, the profits of twinning are different between beef and dairy cattle. Twin births give benefit to beef cattle farming through the increase in total weaning per cattle. The pros and cons of twin births occur in dairy cows farming, especially on milk production.